2003
DOI: 10.1046/j.1445-5994.2002.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a weight‐based heparin nomogram for patients with acute coronary syndromes

Abstract: The current study confirms the marked superiority of the weight-based heparin regimen for treatment of patients with ACS. The nomogram dramatically facilitated the attainment of therapeutic APTT, and may represent the optimal method for titration of heparin dosage to individual heparin requirements in patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
2
21
3
Order By: Relevance
“…Time to achieve threshold aPTT in the control group of our study was comparable to findings of previous studies evaluating standard care weight-base nomogram in nonobese patients (23)(24)(25)(26)(27). Few studies have addressed the issues of UFH dosing in the obese (21,25,(27)(28)(29).…”
Section: Obesitysupporting
confidence: 78%
See 1 more Smart Citation
“…Time to achieve threshold aPTT in the control group of our study was comparable to findings of previous studies evaluating standard care weight-base nomogram in nonobese patients (23)(24)(25)(26)(27). Few studies have addressed the issues of UFH dosing in the obese (21,25,(27)(28)(29).…”
Section: Obesitysupporting
confidence: 78%
“…Interestingly, they did not find a difference in the time to first therapeutic aPTT between obese and nonobese patient. This may be explained by a time to therapeutic aPTT for nonobese patients of 30.0 6 77.0 hours, which is at odd with our results and previous studies (23)(24)(25)(26)(27) involving nonobese patients. This could be since, unlike the present study, most patients in the study from Riney et al (20) did not receive an initial bolus.…”
Section: Obesitycontrasting
confidence: 56%
“…Proposed mechanisms for differences in heparin dosing requirements based on disease state have included differing levels of fibrinogen, cryoprecipitate, vitronectin, platelet factor 4 and differing degrees of platelet activation [23][24][25]. As such, weight based nomograms have been developed for both acute coronary syndromes and venous thromboembolic disease to address the disease specific differences in coagulation [8,9]. Guidelines recommend an intravenous heparin bolus dose of 80 U/kg and an initial infusion rate of 18 U/kg/h in patients with acute venous thromboembolic disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…Supra-and sub-therapeutic levels of anticoagulation can lead to an increased propensity for & Robert O. Roswell roswer01@nyumc.org 1 bleeding and thromboembolic phenomena respectively. When patients at risk for stroke with AF/AFL are hospitalized, physicians often combine their knowledge of UFH nomograms that are available for acute coronary syndrome and venous thromboembolism to best guide initial therapy [6][7][8][9]. Such dosing regimens do not take into account the specific underlying disease process which can alter steadystate heparin requirements [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In 1996, the authors' hospital developed a weight-based heparin protocol. A formal assessment revealed that, relative to traditional non-weight-based dosing, the weight-based protocol was superior in terms of the time required to achieve a minimum level of therapeutic anticoagulation, without an increase in adverse events.…”
Section: Introductionmentioning
confidence: 99%